Skeletal Muscle Transcriptomic Comparison Between Men and Women in Response to Acute Sprint Exercise - Nie, Mingkun; Liu, Qingling; Yan, Cheng (Frontiers in Genetics, 2022)
Abstract: Background: Acute sprint exercise is a time-efficient physical activity that improves cardiorespiratory fitness in younger and middle-aged adults. Growing evidence has demonstrated acute sprint exercise provides equal to or superior health benefits compared with moderate-intensity continuous training, which will dramatically increase aerobic capacity, insulin sensitivity and muscle capillarization. Although the beneficial effects of acute sprint exercise are well documented, the mechanisms behind how acute sprint exercise prevents disease and benefits health are less understood. Method: We obtained differentially expressed genes in muscle from mem and women before and after an acute sprint exercise. Then, we identified hub genes from the protein–protein interaction (PPI) network of DEGs and key transcription factors in men and women related to acute sprint exercise. Finally, KEGG and GO enrichment is performed in DEGs and sex-biased genes, respectively. Results: Firstly, we identified 127 sexually dimorphic gene in men (90 up, 37 down) and 75 genes in women (90 up, 37 down) in response to acute sprint exercise (Figure 2. E, F). Secondly, CEBPB, SMAD3 and CDKN1A are identified as top 3 hub genes related to men-biased. Accordingly, top 3 hub genes related to women-biased genes are JUN, ACTB and SMAD7. In addition, CLOCK, ZNF217 and KDM2B are the top 3 enriched transcriptional factors in men-biased genes. While, XLR, SOX2, JUND and KLF4 are transcription factor enriched most in women-biased genes. Furthermore, based on GO and KEGG enrichment analysis, we identified potential key pathways in regulating the exercise-related response in men and women, respectively. Conclusions: In this study, we found the difference in gene expression and enrichment pathways in muscle from men and women in response to acute sprint exercise. these results will shed new light on the mechanism underlying sex-based differences in skeletal muscle remodelling and metabolism related to sprint interval training, which may illustrate the mechanisms behind how acute sprint exercise prevents disease and benefits health are less understood.